Women and equal opportunity in workplace: A myth orreality? / Norazlan Anual ... [et al.] - Anual, Norazlan; Hj Ariffin, Kamisah; Razali, Azlini; Mohamad, Raihanah (Universiti Teknologi MARA Cawangan Pahang, 2002)
Discrimination is an anti-social offence. It is related to any distinction, exclusion or preference made up on the basis of race, color, sex, religion, political opinion, national extraction or social origin, which has the effect of nullifying or impairing equality of opportunity of treatment in employment or occupation (International Labor Office, 1968). In Malaysia, there has always been a big question whether women holding managerial positions are being discriminated. Although it is difficult to assess the real extent of the discrimination, it is believed to exist. This paper investigates whether this kind of discrimination occurs in workplace with a focus on female executives in private sectors.